2017
DOI: 10.1371/journal.pone.0187569
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and exosome mediated molecular defense mechanism in bovine granulosa cells exposed to oxidative stress

Abstract: Various environmental insults including diseases, heat and oxidative stress could lead to abnormal growth, functions and apoptosis in granulosa cells during ovarian follicle growth and oocyte maturation. Despite the fact that cells exposed to oxidative stress are responding transcriptionally, the potential release of transcripts associated with oxidative stress response into extracellular space through exosomes is not yet determined. Therefore, here we aimed to investigate the effect of oxidative stress in bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 81 publications
11
97
0
Order By: Relevance
“…Finally, it is known that embryos release EVs during the early embryonic development (Saadeldin et al, ) but there is still controversy regarding the function of embryo secreted vesicles and its consequences on further development (Mellisho et al, ). The release of EVs by the embryos and the content of these vesicles, especially miRNAs, undergo several changes, which may be caused by the culture conditions directly on the embryo or influenced by the cells present in the microenvironment, in alignment with previous reports that oxidative stress can alter the composition of granulosa cells from the EVs (Saeed‐zidane et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…Finally, it is known that embryos release EVs during the early embryonic development (Saadeldin et al, ) but there is still controversy regarding the function of embryo secreted vesicles and its consequences on further development (Mellisho et al, ). The release of EVs by the embryos and the content of these vesicles, especially miRNAs, undergo several changes, which may be caused by the culture conditions directly on the embryo or influenced by the cells present in the microenvironment, in alignment with previous reports that oxidative stress can alter the composition of granulosa cells from the EVs (Saeed‐zidane et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…Accordingly, our results indicated that the higher number and bigger size EV (Figure c) were found in spent media of male embryos cultured under high oxygen level. Similar results were obtained in our previous study in granulosa cells exposed to OS (Saeed‐Zidane et al, ). In contrast, the female embryos exhibited a lower number and bigger size EVs upon exposure to OS.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figure , EVs from male embryos at higher oxygen level contained higher level of NFE2L2 and SOD1 transcripts compared to those cultured under low oxygen level, which might be beneficial of development of embryos (Pavani et al, ). The role of EVs is not only in cell–cell communication (Saeed‐Zidane et al, ) but also in the removal of undesirable cellular molecules (Takahashi et al, ). Contrary to cellular expression, the NOTCH1 was increased in EVs derived from male embryos exposed to OS compared with female counterparts, which may indicate the selectivity of cargo molecules to be exported by EVs (Bhome et al, ; Hinger et al, ) to facilitate cell to cell communication or maintain of cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting these data, other authors [30] demonstrated that increased 8OHdG concentrations in the FF of women undergoing IVF are associated with oocyte degeneration, suggesting that oxidative stress in the follicular compartment has deleterious effects on the oocyte. Our data are in agreement with a report showing lower vitamin E concentrations in the FF of women with infertility related to endometriosis [31] but are in contrast with another study reporting both increased 8OHdG and an higher vitamin E concentration in the FF of women with endometriosis. These data probably indicate an up-regulation of the follicular antioxidant system in an attempt to neutralize, but not successfully, reactive species and to prevent oxidative damage to oocytes.…”
Section: Discussionsupporting
confidence: 92%